Characterization and identification of lipid-producing microalgae species isolated from a freshwater lake - Abou-Shanab, Reda A. I.; Matter, Ibrahim A.; Kim, Su-Nam; Oh, You-Kwan; Choi, Jaeyoung; Jeon, Byong-Hun (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Microalgal lipids are the oils of the future for sustainable biodiesel production. One of the most important decisions in obtaining oil from microalgae is the choice of species. A total of 45 algal cultures were isolated from a freshwater lake at Wonju, South Korea. Five microalgal isolates were selected based on their morphology and ease of cultivation under our test conditions. These cultures were identified as strains of Scenedesmus obliquus YSL02, Chlamydomonas pitschmannii YSL03, Chlorella vulgaris YSL04, S. obliquus YSL05, and Chlamydomonas mexicana YSL07 based on microscopic examination and LSU rDNA (D1-D2) sequence analysis. S. obliquus YSL02 reached a higher biomass concentration (1.84 +/- 0.30 g L-1) with a lower lipid content (29% w/w), than did Chla. pitschmannii YSL03 (maximum biomass concentration of 1.04 +/- 0.09 with a 51% lipid content). Our results suggest that Chla. pitschmannii YSL03 is appropriate for producing biodiesel based on its high lipid content and oleic acid proportion. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: FATTY-ACID; BIODIESEL; EXTRACTION